Downregulation of Ripk1 and Nsf mediated by CRISPR-CasRx ameliorates stroke volume and neurological deficits after ischemia stroke in mice - Song, Xincheng; Lan, Yang; Lv, Shuang; Wang, Yuye; Chen, Leian; Lu, Tao; Liu, Fei; Peng, Dantao (Frontiers in Aging Neuroscience, 2024)
Necroptosis is implicated in the pathogenesis of ischemic stroke. However, the mechanism underlying the sequential recruitment of receptor-interacting protein kinase 1 (RIPK1) and Nethylmaleimide-sensitive fusion ATPase (NSF) in initiating necroptosis remains poorly understood, and the role of NSF in ischemic stroke is a subject of controversy. Here, we utilized a recently emerging RNA-targeting CRISPR system known as CasRx, delivered by AAVs, to knockdown Ripk1 mRNA and Nsf mRNA around the ischemic brain tissue. This approach resulted in a reduction in infarct and edema volume, as well as an improvement in neurological deficits assessed by Bederson score, RotaRod test, and Adhesive removal test, which were achieved by RIPK1/receptorinteracting protein kinase 3/mixed lineage kinase domain-like protein signaling pathway involved in neuronal necroptosis. In conclusion, the downregulation of Ripk1 mRNA and Nsf mRNA mediated by CRISPR-CasRx holds promise for future therapeutic applications aimed at ameliorating cerebral lesions and neurological deficits following the ischemic stroke.